2014
DOI: 10.1002/bdd.1880
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear pharmacokinetics of factor VIII and its phosphatidylinositol lipidic complex in hemophilia A mice

Abstract: Factor VIII (FVIII) is an important cofactor in the blood coagulation cascade and its deficiency or dysfunction causes Hemophilia A (HA), a bleeding disorder. Replacement with recombinant FVIII is limited by a short half-life and the development of inhibitory antibodies. We have developed a phosphatidylinositol (PI) containing lipid nanoparticle that, when associated with FVIII, reduces immunogenicity and prolongs circulation of the therapeutic protein in HA mice. Here, we conducted a multiple dose level pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…The PK profile of BDD FVIII in antibody‐negative HA mice is well described by a one‐compartment model with Michaelis–Menten (MM) elimination as reported previously . It was proposed that this non‐linearity in FVIII PK in HA mice is due to saturable clearance of the protein via its primary clearance receptor, low‐density lipoprotein receptor‐related protein (LRP) .…”
Section: Methodssupporting
confidence: 52%
“…The PK profile of BDD FVIII in antibody‐negative HA mice is well described by a one‐compartment model with Michaelis–Menten (MM) elimination as reported previously . It was proposed that this non‐linearity in FVIII PK in HA mice is due to saturable clearance of the protein via its primary clearance receptor, low‐density lipoprotein receptor‐related protein (LRP) .…”
Section: Methodssupporting
confidence: 52%
“…This method combines allometry‐based scaling of PK parameters with normalized Wajima curves from preclinical species to generate human concentration–time profiles. The suitability of this method to scale PK of modified FVIII products has been previously demonstrated . Briefly, parameter estimates of V ss and CL in mice were obtained by fitting of a 1 compartment, linear clearance model to PK data.…”
Section: Methodsmentioning
confidence: 99%
“…The suitability of this method to scale PK of modified FVIII products has been previously demonstrated. 30,32 Briefly, parameter estimates of V ss and CL in mice were obtained by fitting of a 1 compartment, linear clearance model to PK data. MRT and C ss were calculated as MRT = V ss /CL and C ss = dose/V ss .…”
Section: Pk Modeling and Allometric Scalingmentioning
confidence: 99%
“…However, following 4 IU/kg injections, D519V/E665V was reproducibly detected up to 2 h, but WT could not be recovered in any samples even as early as 5 min. We have previously reported that the PK of full length FVIII as well as the B-domain deleted WT protein is non-linear in the HA mice used in these studies (21,24). This is also apparent from the fact that non-compartmental analyses show an increase in clearance at lower doses (it is appropriate to acknowledge here that the PK could have been inadequately estimated at lower doses due to limited recovery of plasma FVIII levels at these doses).…”
Section: Pharmacokinetic Studiesmentioning
confidence: 99%